Synthesis of aromatic polyimides from dianhydrides and diamines. - Harris, F. W.
Although the first synthesis of an aromatic polyimide was carried out in 1908 [1]it was not until the late 1950s that high molecular weight polymers were prepared [2-4]. Perhaps more surprising is that even today the most common method for their synthesis, i.e. the treatment of an aromatic diamine with an aromatic tetracarboxylic acid dianhydride, is still not completely understood. This is because the course of the reaction, which is carried out by both two-and one-step methods, is dramatically affected by the reaction conditions [5]. Even the mode of monomer addition can affect the molecular weight of the polymer obtained [6, 7]. In the following paragraphs the complexities of the sequence of events leading to the polyimide structure will be thoroughly examined.
Keywords: MOLECULAR WEIGHT DISTRIBUTION; AMIC ACID; AROMATIC POLYIMIDE; FAVOURABLE CONFORMATION; THERMAL IMIDISATION